2005
DOI: 10.1037/0021-9010.90.6.1044
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation-Level Theory, Opponent Process Theory, and Dispositions: An Integrated Approach to the Stability of Job Satisfaction.

Abstract: Research suggests that the stability of job satisfaction is partially the result of dispositions (J. J. Connolly & C. Viswesvaran, 2000; C. Dormann & D. Zapf, 2001; T. A. Judge & J. E. Bono, 2001a; T. A. Judge, D. Heller, & M. K. Mount, 2002). Opponent process theory (R. L. Solomon & J. D. Corbit, 1973, 1974) and adaptation-level theory (H. Helson, 1948) are alternative explanations of this stability that explain how environmental effects on job satisfaction dissipate across time. On the basis of an integratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
80
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(87 citation statements)
references
References 87 publications
1
80
0
Order By: Relevance
“…This leads to feelings of emotional attachment and being at home and more comfortable with their occupation. Research has shown that dispositions influence the way in which employees perceive their occupation, which consequently affects their occupational satisfaction (Bowling, Beehr, Wagner, & Libkuman, 2005) and ultimately translating into higher OCC. This finding extends current employee-organizational relationships literature (Masterson, Lewis, Goldman, & Taylor, 2000;Settoon, Bennett, & Liden, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…This leads to feelings of emotional attachment and being at home and more comfortable with their occupation. Research has shown that dispositions influence the way in which employees perceive their occupation, which consequently affects their occupational satisfaction (Bowling, Beehr, Wagner, & Libkuman, 2005) and ultimately translating into higher OCC. This finding extends current employee-organizational relationships literature (Masterson, Lewis, Goldman, & Taylor, 2000;Settoon, Bennett, & Liden, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have found that people high in trait NA are more sensitive to negative events, whereas people high in trait PA are more sensitive to positive events (e.g., Brief, Butcher, & Roberson, 1995;Larsen & Ketelaar, 1989. Conversely, it is possible that people respond similarly to workplace events but the person's disposition influences how quickly they return back to their baseline after an event (Bowling et al, 2005). Dispositions may also be responsible for determining one's job satisfaction baseline, also referred to as a "set point" or adaptation level (Bowling et al, 2005).…”
Section: Traditional Approaches To Studying the Antecedents Of Job Samentioning
confidence: 99%
“…Indeed it may be that the perceptions of the job environment have more influence on job satisfaction than do objectively measured job characteristics themselves (Judge, Locke, Durham, & Kluger, 1998). Also, Bowling, Beehr, Wagner, and Libkuman (2005) suggest that stable dispositions may affect employees' responses to workplace events. Researchers have found that people high in trait NA are more sensitive to negative events, whereas people high in trait PA are more sensitive to positive events (e.g., Brief, Butcher, & Roberson, 1995;Larsen & Ketelaar, 1989.…”
Section: Traditional Approaches To Studying the Antecedents Of Job Samentioning
confidence: 99%
“…Gamero (2005) also states that job stability and promotion opportunities have a strong impact on job satisfaction. Bowling et al (2005) present several alternative theories of stability and explain how the environmental effects on job satisfaction dissipate over time.…”
Section: Stability and Employabilitymentioning
confidence: 99%